Metacognitive strategy instruction and bilingual readers' comprehension of expository texts - Tupe, Buenavida A. (2008)
This study investigated the ways of which explicit instruction in the metacognitive strategies affected the reading comprehension of third year bilingual high school students. Both qualitative and quantitativelv measures were used to determine the results of the study. Results revealed that after the intervention, there was a difference in their reading comprehension. In general, the findings of this study support the assertion that language affects comprehension (Arafat's, 1996), and the language skills enhance or enable the effectiveness of the use of metacognitive strategies for comprehension (van Gelderen et al, 2007)